Determination of Empiric Antibiotic Therapy in Community-acquired Complicated Urinary Tract Infection - Zehra Karacaer (Ankara Üniversitesi Tıp Fakültesi Mecmuası, 2020)

(untitled)
Objectives:Complicated urinary tract infection (UTI) is caused by gram negative bacteria; among them, Escherichia coli is the most common. The increase in antibiotic resistance rates of common agents decreases the empirical treatment options. The aim of this study was to investigate the concordance of empirical antibiotic treatment in complicated UTI patients who were followed up in our clinic in the last two years.Materials and Methods:This study was conducted as a descriptive retrospective study between 01.01.2017 and 01.01.2019. Demographic, laboratory and clinical data of the patients were obtained by scanning files or automation systems. If the microorganism was sensitive to empirical antibiotic treatment the situation was defined as concordance of treatment.Results:In our study, 102 patient files were examined and 74 were excluded from the study. Of the 28 patients, 19 (67.9%) were male. The mean age of the patients was 58.18±19.98 years. E. coli was the most frequently isolated agent. As empirical treatment cephalosporins and carbapenems were mostly preferred. When all antibiotics are evaluated together, it is seen that 53.6% of the empirical antibiotic treatments are concordance with culture results. The suitability rates for carbapenems and cephalosporins, which are the most commonly used antibiotics, were 46.7% and 60%, respectively.Conclusion:According to the results of this study, our empirical treatment choices are suitable in the treatment of complicated UTI. However, it may be a rational approach to prioritize cephalosporins in similar situations in our center.